2019
DOI: 10.1038/s41416-018-0364-7
|View full text |Cite
|
Sign up to set email alerts
|

HPV, tumour metabolism and novel target identification in head and neck squamous cell carcinoma

Abstract: Background Metabolic changes in tumour cells are used in clinical imaging and may provide potential therapeutic targets. Human papillomavirus (HPV) status is important in classifying head and neck cancers (HNSCC), identifying a distinct clinical phenotype; metabolic differences between these HNSCC subtypes remain poorly understood. Methods We used RNA sequencing to classify the metabolic expression profiles of HPV +ve and HPV −ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 48 publications
2
50
0
Order By: Relevance
“…In the present study, differences between SUVmax or SUVmean and HPV or p16 presence were insignificant. Comparable results have been obtained in other studies, where no differences in SUVmax values between p16-and HPV-positive, and p16-and HPV-negative patients were reported [40][41][42]. By contrast, Schouten et al demonstrated that SUVmax in HPV-positive tumors was significantly lower than in HPV-negative tumors [43].…”
Section: Discussionsupporting
confidence: 52%
“…In the present study, differences between SUVmax or SUVmean and HPV or p16 presence were insignificant. Comparable results have been obtained in other studies, where no differences in SUVmax values between p16-and HPV-positive, and p16-and HPV-negative patients were reported [40][41][42]. By contrast, Schouten et al demonstrated that SUVmax in HPV-positive tumors was significantly lower than in HPV-negative tumors [43].…”
Section: Discussionsupporting
confidence: 52%
“…Previous studies indicate that HPV+ HNSCC is more reliant on oxidative phosphorylation as an energy source than HPV-HNSCC [15]. Oxidative phosphorylation requires electron transport via mitochondrial cellular respiratory complexes I-IV [17].…”
Section: Low Expression Of Genes Encoding Multiple Components Of the mentioning
confidence: 99%
“…Increased expression of the monocarboxylic acid transporter family member, SLC16A1 (MCT1) was recently reported to be associated with poor survival outcomes in HNSCC [15]. Although, expression of SLC16A1 was significantly higher than normal head and neck tissues for both HPV+ and HPV-HNSCC, and expression of SLC16A1 was higher in HPV-HNSCC than HPV+ HNSCC, the impact of differential expression of SLC16A1 on overall survival in either HPV+ or HPV-HNSCC was not significant (p > 0.05).…”
Section: Low Expression Of Slc16a2 a Thyroid Hormone Transporter Inmentioning
confidence: 99%
See 2 more Smart Citations